The more you know, is it better? School and sexual and reproductive health - Seidmann, Susana; Di Iorio, Jorgelina; Azzollini, Susana; Rolando, Silvana (Revista Diálogo Educacional, 2014)
The ratification of the Law 26.150 in Argentina, in the year 2006, established the National Program of Integral Sexual Education, by which all children at school “have the right to receive integral sexual education at public schools, in state or private institutions, in national, province, Autonomous City of Buenos Aires and city´ s territories”. Sexual education appears as a “new” content in a scholar structure that has to suit its teaching practices to demands perceived as external and imposed. In the frame of a research about social representations of teaching practices, there appeared some difficulties and tensions at schools related to the teaching of the contents of sexual integral education. 21 depth interviews with teachers were accomplished in the City of Buenos Aires´, Argentina, high schools. The main thematic axes were the teaching practices related to sexual integral education, the obstacles and opportunities of sexual integral education. Through emergent categories, the material was analyzed through the comparative constant method. The teaching practices are organized as a complex and heterogeneous interaction field, in which teachers´ everyday life develops, which permits to define school as a place of meaning negotiation. It is important to think about teaching practice because it permits to clear up ideas and assumptions which work as an efficacy condition of the scholar device.